A study on user acceptance of the ip timetrack at Petronas Carigali Sdn Bhd / Mohd Syahrizat Mohd Kamal - Mohd Kamal, Mohd Syahrizat (Universiti Teknologi MARA,Terengganu, 2010)
The aim of this study was to explore the relationship between perceived ease of use and perceived usefulness with user acceptance of the implementation of iP timetrack in the organization. Furthermore, it is also important to the researcher to examine if there is any difference in terms of user acceptance of the system between executive and non executive. Dependent variable in this research is user acceptance of iP timetrack at Petronas CariGali Sdn Bhd while independent variables are perceived ease of use and perceived usefulness. Actually, both independent variables are arising from Technology Acceptance Model. Davis is a person who is responsible to create Technology Acceptance Model in 1989. A survey questionnaire was used for data collection. Besides, an informal interview with selected respondents was conducted to get additional information regarding iP timetrack system. Total of respondents involved in the research were 50 and the respondents came from non technical department which mean not involved directly with the production of oil and gas such as administration, supply chain management, human resource management and finance and accounting department. The results from the survey were recorded by using Statistical Package for Social Science (SPSS) version 14.0 software. The researcher was used frequency distribution, reliability analysis, t-test, and Spearman correlation to test all data from the questionnaire. All results and analysis with an interpretation was been explain in chapter finding and analysis.